Microbial synergistic interactions enhanced power generation in co-culture driven microbial fuel cell - Islam, M. Amirul; Karim, Ahasanul; Mishra, Puranjan; Dubowski, Jan J.; Yousuf, Abu; Sumaya, Sarmin; Khan, Maksudur R. (Elsevier B.V., 2020)
An understanding of the inter-species relationships, especially their metabolic network in a mixed-culture system, is crucial to design an effective inoculum for enhancing the power generation of wastewater fed microbial fuel cell (MFC). In the present study, the influence of microbial mutualistic interactions on the power generation of palm oil mill effluent fed MFCs has been widely investigated by designing several co-culture and mixed culture inoculums. Among the different inoculum compositions, the highest power density of 14.8 W/m3 was achieved by Pseudomonas aeruginosa and Klebsiella variicola co-culture inoculum due to their synergistic relationships which were inter-linked via fermentation-based metabolites. Besides, the interaction of K. variicola and Bacillus cereus positively influenced the power generation resulting in a maximum power density of 11.8 W/m3 whereas the antagonistic relationship between B. cereus and P. aeruginosa resulted in a lower power generation of 1.9 W/m3. The microbial mutualistic interactions were investigated with polarization, cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), as well as by using metabolite and biofilm analysis. It was observed that the synergism between bacteria enhanced power generation through the production of higher electron shuttling mediators and efficient biofilm formation as evidenced by polarization, CV and EIS analysis. In contrast, the antagonistic relationship resulted in production of cell inhibiting metabolites leading to the formation of ineffective biofilm. These findings demonstrate that the synergistic interaction between or within microorganisms is emergent in designing co-culture or mixed-culture inoculum for achieving maximum power generation in MFCs.